KONTRIBUSI KOMPETENSI PEDAGOGIK GURU TERHADAP KETERAMPILAN BERPIKIR RASIONAL SISWA DALAM PEMBELAJARAN EKONOMI SMA SE-KABUPATEN PASER KALIMANTAN TIMUR - Khairuddin Khairuddin (Universitas Lambung Mangkurat, 2013)
This research to reveal the contribution of teachers to the pedagogical rational thinking ability of students in the learning economy Pedagogical competence is basic pedagogical competence inherent in a teacher. This Competence is fundamental to the self-image of teachers as part of the natural community. Teachers are designers of children’s future. The study used survey method. This is to be expected as a result of the teaching profession through pedagogical competence. The fact that the economy has been less lead students toward developing the ability to think rationally in an economy such as life saving, saving, efficient, productive, prioritize needs, economical, and allocate limited resources to fullfil the needs. Most teachers prefer the ability to memorize material or concept learning, but for the life of the future filled with uncertainty, students need the skills to apply the concept of economic concepts into their daily lives in the community. This study used survey method to a senior high school of a Paser district of the east borneo. There are 546 students of class XI Social sciences from eight senior high schools in the population and take a random sample many as 231 students. This study used questionnaires as the data collection instrument.Key words: Pedagogy competences, rational thinking, learning economic